The Analysis Study of Relationship of Breast Arterial Calcifications on Mammography to Predict Elevated Risk of Coronary Artery Disease: A Comprehensive Systematic Review - Rendi Rafsanjani; Bintara Ayu Putri; Mutiara Nurul Mahabbah (The International Journal of Medical Science and Health Research, 2025)
Background: Breast arterial calcifications (BAC) are medial arterial calcifications visualized as linear "tram-track" deposits in the breast vasculature on mammograms. Women with BAC have been found to have higher coronary artery calcium (CAC) scores and increased prevalence of cardiovascular risk factors such as diabetes, hypertension, and chronic kidney disease. This systematic review aims to comprehensively evaluate the current evidence on the relationship between BAC and CAD risk.  Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2015 to 2025. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: The relationship between BAC and CAD is well-supported by retrospective studies, demonstrating significant associations with coronary calcification, cardiovascular risk factors, and disease severity. While BAC may not serve as a standalone diagnostic tool, its potential as an adjunct marker for CAD risk stratification is promising.